O impacto da capacidade de inova????o e da experi??ncia internacional no desempenho exportador de PMES industriais brasileiras - Oura, Maur??cio Massao (2014)
The overall objective of this thesis is to investigate the impact of the innovation capacity and international experience on the export performance of Brazilian industrial SMEs, seeking to answer the following question: What is the impact of the innovation capacity and international experience on the export performance of Brazilian industrial SMEs? Specifically, the objective was to identify which of the two factors is more relevant for export performance. The research is regarded as explanatory, quantitative and causal. The data were analyzed in light of the Resource Based View, Dynamic Capabilities Based View and results of empirical research on the topic. Data were analyzed using the technique of Structural Equation Modeling, using the method of Partial Least Squares (PLS) in SmartPLS software, and additional tests were performed in SPSS software using the method of Ordinary Least Squares (OLS). The sample consisted of 112 small and medium enterprises of the southeastern region of Brazil. The results indicate that the impact of the international experience is greater than the innovation capacity on export performance, confirming the thesis of this research. The moderating effects of the variables technological intensity, level of economic development and perceived legitimacy pressure were also analyzed, but these variables do not show statistical significance. The work ends with the concluding remarks, limitations of the study and suggestions for future studies.